(untitled) (Research, Society and Development, 2022)
This study suggests that pirarucu is a fish capable to have competitive products in the national premium fish market and analyze the opportunities and constraints of this supply chain in Brazil. To achieve that, a semi-structured interview was conducted with 22 players of the cultivated pirarucu supply chain in Brazil, resulting in more than 13 hours of dialogue to understand who the players are, and the main challenges and opportunities for this market. The pirarucu products (such as frozen fillet and loin) are premium products and can become competitive in the niche market of value-added fish, if their constraints are overcome, since they have intrinsic potentialities and extrinsic values to the consumer. The non-conformity of the information added to the lack of knowledge about the species were identified as the main limitations of the organization of the supply chain. Fish farmers show interest in strengthening the cultivated pirarucu supply chain. The processing industry and the consumers demand a regular supply, and input suppliers realize that this is an important national market. In any case, there is a market for premium pirarucu, and it is noticeable that there is a demand for superior quality fish, and pirarucu presents several characteristics valued by the consumer.